Nutritional Quality of Three Iron-Rich Porridges Blended with Moringa oleifera, Hibiscus sabdariffa, and Solanum aethiopicum to Combat Iron Deficiency Anemia among Children - Brice Ulrich Foudjo Saha; Aphrodite Tchewonpi Choumessi; Alvain Meshi Ayamo; Ronald Blaise Mouafo Kuagny; Ismael Teta; Edouard Akono Nantia; Richard Aba Ejoh (Journal of Food Quality)
Iron deficiency anemia has been a public health issue in children under five years of age in Cameroon. Very limited attempts have been carried out to develop an iron-rich food using local ingredients. The study aimed at developing functional porridges from local ingredients for iron-deficient children aged 6–23 months. Leaves of Moringa oleifera, Hibiscus sabdariffa, and Solanum aethiopicum were harvested as sources of iron, dried, ground into powder, and screened for their water and iron contents. Each vegetable powder was mixed with the other ingredients (dry whole milk, brown sugar, yellow maize flour, and refined soybean oil) to obtain three powdered porridges using linear programming (LP). Protein, lipid, carbohydrate, iron, energy, water, ash, crude fiber, and vitamin C contents, expressed in dry weight, were determined on powdered porridges. Powdered porridges were cooked in boiled water (ratio 2 : 7%w/w) for 5 min. Hedonic tests were conducted using cooked porridges with 50 untrained panelists. Leaf powders contained iron varying between 5.39 and 5.98 mg/100 g. LP models of the three porridges satisfied the nutritional requirements of children aged 6–23 months in terms of iron, lipid, protein, carbohydrate, and caloric daily intake. Protein, lipid, carbohydrate, iron, energy, water, ash, crude fiber, and vitamin C contents were, respectively, between 11.37 and 13.83 g/100g, 30.79 and 32.94 g/100g, 45.97 to 46.81 g/100g, 5.14 and 6.15 mg/100g, 509.93 and 517.48 kcal/100g, 6.42 to 7.62 g/100g, 2.20 and 2.88 g/100g, 1.65 and 2.44 g/100g, and 46.49 and 163.38 mg/100g. The cost of powdered porridges varied between 0.40 and 0.49 USD/100g. The sensory analysis showed that the moringa leaf-based porridge (82%) was the most appreciated followed by eggplant leaf-based porridge (80%) and folere leaf-based porridge (70%). Hence, these results showed that moringa, folere, and eggplant leaves can be used in functional foods to alleviate iron deficiency among children aged 6–23 months.